Determination of Power Value Effect in Laser Welding Method on Strength of AISI 430 Ti Stainless Steel (International Journal of Scientific Research and Management (IJSRM), 2020)
Laser is a device that means light amplification by stimulated emission of radiation, can be obtained in various ways and strengthens electromagnetic heat. The usage area of ​​titanium alloys has been limited to only special production vehicles in recent years due to their high costs. Today, one of the most advantageous metals for the automotive and aerospace industry due to the advances in production techniques and low weight and high resistance against corrosion. Laser welding method is one of the most important joining techniques due to its fixed properties. Power value one of the most effective parameter for joint strength. In this study, the effect of power factor on joint strength during the welding process of AISI 430 Ti stainless sheet was investigated. According to tensile test trials, observed that the rupture strength increases with the parameter of increased laser power but the value has been down after a certain point.